Functions of Parental Intergenerational Narratives Told by Young People. (21st June 2018) - Merrill, Natalie; Booker, Jordan A.; Fivush, Robyn
Abstract: Family stories help shape identity and provide a foundation for navigating life events during adolescence and early adulthood. However, little research examines the types of stories passed onto adolescents and emerging adults, the extent to which these stories are retained and accessible, and the potentially influential parental‐ and self‐identity content constructed in telling these stories. Across three samples, we investigate the accessibility and functions of intergenerational narratives that adolescents and emerging adults know of their parents. By examining adolescents' open‐ended intergenerational stories, emerging adults' intergenerational stories of parents' transgression and proud moments, and emerging adults' intergenerational stories of parents' self‐defining moments, we systematically describe the functions of various intergenerational stories during adolescence and early adulthood, when identity is in formation. We found that adolescents and emerging adults can readily recount intergenerational stories from parents, and that many of these stories serve to build relationships with the parent, provide insights about parents, provide insights about self, and transmit life lessons. The specific findings by narrative topic and by gender of both participant and parent are discussed. Abstract : Merrill, Booker and Fivush examine the social functions associated with transmitting intergenerational narratives to adolescents and emerging adults and how these family stories affect identity formation in early adulthood. Merrill et al. observed that the intergenerational stories of parents' transgression and proud moments told by adolescents and emerging adults operate as a way to transmit life lessons, strengthen relationships with the parent and give insights into their parents and their self.